Flexible graphene/mxene composite thin films for high-performance electromagnetic interference shielding and joule heating - Li, Hongling (2024)
The development of flexible films with excellent electromagnetic interference (EMI) shielding and enhanced thermal management capabilities is highly desired to meet the ever-growing demands for portable and miniaturized electronics. Herein, graphene/MXene (G/M) composite thin films with unique structure, excellent flexibility, and outstanding EMI shielding capability are fabricated by integrating MXene nanosheets with a three-dimensional porous graphene film via a facile vacuum-assisted filtration method. Notably, the obtained G/M composite thin film with a thickness of 100 μm possesses a high EMI shielding effectiveness of up to 96.3 dB. This remarkable EMI shielding performance is attributed to the synergistic effect between the wrinkled structure of the MXene layer and the interconnected porous network of the graphene film, thereby ensuring excellent electrical conductivity and superior mechanical properties. Additionally, the polymer-modified G/M composite thin film shows an excellent electrothermal conversion capability under a low driving voltage. This work provides a facile strategy for fabricating flexible composite thin films toward practical EMI shielding and thermal management applications in next-generation miniaturized flexible electronics.